The Familiarity Effect in Prioritizing Distant Solutions: A Discrete Choice Experiment on Development Planners in Indonesia - Siahaan, Timothy Pieter Christian (UI Scholars Hub, 2025)
Development planning ideally requires accurate information to translate distant solutions, where actions and impacts are separated by significant delays. However, the attention theory suggests that the attention of planners is constrained by familiarity bias, shaped by organizational procedures and communication channels. This study argues that planners are less likely to prioritize distant solutions due to a stronger sense of perceived self-efficacy. Even when presented with favorable information, decision-makers tend to rely on heuristics that filter out unfamiliar information. Employing a mixed-method approach by combining a discrete choice experiment and qualitative interviews with regional planners in Indonesia, this study discovers that familiarity bias influences decision-making. Planners not only adjust decisions based on human resource capacities but also favor familiar performance indicators drawn from the common information inventory. This study advances the attention theory and the behavioral approach in public sector decision-making, particularly in addressing new development challenges such as energy transitions and the adoption of artificial intelligence (AI). By focusing on a developing country, this study bridges the development theory and practice in a more human-centered and critical context.